THE UNIQUENESS OF TRADITIONAL FOOD AT THE DUKUTAN CEREMONY AS CULINARY TOURISM - Wahyu Tri Hastiningsih; A Anditha Sari; Faridah Hanim Ismail (International Journal of Social Science, 2024)
Tourist visits in Central Java have increased, especially in 2022. One of the efforts is to conduct tourism performances. Performances and culture as part of tourism that needs to be preserved for the sustainability and continuity of future generations to be enjoyed. Nglurah village with its special event, Dukutan, is a ritual village cleanup event in the Menggung temple area using traditional Javanese clothing that serves traditional food called Gandik. From the results of previous research, that Gandik is only as a dish. In addition, a more in-depth discussion is only on the ritual of the ceremony so that it is not found specifically about the selling value of Gandik which has a unique value as a selling point to attract tourist visits. This research uses a qualitative method through observation and in-depth interviews with the caretaker of the dukutan event and directly related stakeholders. . The results of this study show that the uniqueness of Gandik is in terms of naming this food served using unique Javanese language with various meanings and purposes. The processing of this food is also not arbitrarily made without any rituals or the implementation of special conditions. The presentation must also use banana leaves in the form of a takir on a tampah